PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERLIBATAN SISWA PADA PEMBELAJARAN MATEMATIKA DI SD NEGERI 76 SUNGAI BULUH - Syafitri, Arini; Mayangsari, Puspitri; Enjelina, Della; Destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The results of this research include initial data or initial conditions obtained by researchers from the results of daily tests of class IV/2 students at SD Negeri 76 Sungai Buluh for the 2024/2025 academic year, then improvements were made using two cycles of Classroom Action Research (PTK) in which there were four stages in each cycle, namely planning, implementation, observation and reflection. This classroom action research is an effort to improve students' mathematical understanding in class IV/2 mathematics using the Problem Based Learning (PBL) model. Based on the known values ​​in cycle 1 of the flat building material, of the 13 students there were only 4 students who met the score > KKM (70) while 9 of them had the score < KKM (70). Based on the known values ​​in cycle 2 of the integer material, of all 13 students there were only 10 students who met the score > KKM (70) while 3 of them had the score < KKM (70). The completeness of individual learning results in cycle I was 4 students with classical completeness reaching 30.77% and the class average score was 64.54. Furthermore, the completeness of individual mathematical understanding in cycle II increased, namely by 10 students with classical completeness reaching 76.92% and the average class score obtained was 82.38. Based on the table of student observation results, the value for Cycle 1 was 77%, Cycle 2 was 100%.   Keywords: flat figures, integer material, problem based learning model